ELISA competitivo para detecção de imunoglobina antiprototoxina epsilon produzida pelo Clostridium perfringens tipo D - Patricia Martins Parreiras (2001)
Standardized the competitive ELISA to detect antibodies against epsilon prototoxins produced by Clostridium perfringens type D as an alternative to replace the method of neutralization in mice for potency testing of vaccines. The plates were sensitized with protoxines epsilon, purified on a column of DEAE - Sepharose CL 6B equilibrated with 0.01 M phosphate buffer pH 7.2. The sera tested by inhibiting the ability to standardize the ELISA reaction between immunoglobulin and rabbit protoxines espsilon. The power of the test serum was calculated from a standard curve prepared with the International Standard imonoglobulina antiespsilon. Sera from cattle vaccinated against C. perfringens types C and D were tested by sononeutralização in mice and by competitive ELISA and the correlation coefficient was 0.87. The applicability and repeatability of the test was measured using a standard curve previously prepared using serum tested on different days and compared with the neutralization test in mice. The correlation coefficient was 0.94.